Olahan Teh Dan Keripik Kelor Sebagai Anti Oksidan Bagi KesehatanDalam Meningkatkan Sistem Imun - Alfina Baharuddin; Suharni A. Fachrin; Yuliati Yuliati; Nia Karuniawati (Window of Community Dedication Journal, 2024)
Moringa is loaded with phytonutrients, which are plant-based nutrients believed to have health-supporting effects. The partner problems are: There is still low public knowledge about the diversification of moringa leaf processing into advanced processed products, so an activity is needed that can increase public knowledge about various processed products that can be developed from moringa so that the economic value of moringa leaves can be increased, Moringa leaves have a lot of nutritional content that is good for the body, and are still underutilized by farmers, especially housewives.... Lack of development of moringa potential as an alternative food source and processed substitute for various kinds of food products.  The need for innovation of highly nutritious processed menus using local raw materials (Moringa) in order to produce superior products.  The level of consumer interest in moringa product processing and moringa powder capsules has not been found. The solutions offered are: Application of appropriate technology in the form of techniques for utilizing environmentally friendly natural ingredients, Counseling on natural ingredients as an effort to increase community knowledge and understanding of the importance of utilizing natural ingredients in everyday life, Training on appropriate technology for making moringa tea as an antioxidant drink Extension method in the form of video playback on the technique of making TEKOR (moringa tea)